Environmental, Social, Governance (ESG) Performance and Capital Structure: The Role of Good Corporate Governance - Muhammad Madyan; Saraswati Kuntum Widuri (Journal of Theoretical and Applied Management (Jurnal Manajemen Teori dan Terapan), 2023)
Objective: The purpose of this study is to investigate the impact of Environmental, Social, and Governance (ESG) performance on capital structure, using good corporate governance (GCG) as a moderating variable. Design/Methods/Approach: The sample comprises companies listed on the IDX outside the financial sector that issued financial and sustainability reports between 2017 and 2021. The Global Reporting Initiative (GRI) index measures ESG performance, the capital structure is measured by leverage, and the moderating variable of good corporate governance is measured by independent commissioner proportion. The data are analyzed using the OLS regression technique. Findings: According to the estimation results, ESG performance positively affects the capital structure of non-financial enterprises. Furthermore, good corporate governance does not moderate the relationship between environmental, social, governance, and capital structure.   Originality/Value: By focusing on ESG performance and capital structure as evaluated in emerging countries, this study adds to existing research on environmental and social performance and its impact on capital structure. Furthermore, GCG is included as a moderating variable in this study. Practical/Policy implication: Based on the findings, it is suggested that firm executives take steps to expand their ESG practices. This ensures sustainability and increases investor and creditor confidence, resulting in more efficient funding sources for the company.